Profissionalidade docente na educação do campo - Lopes, Wiama de Jesus Freitas (2013)
This thesis entitled "Professionalism in Teacher Rural Education analyzes the process of formation of the teaching profession of educators in the field of Breves riversidemultigrade classes on the island of Marajó, state of Pará, through the subject matter of teaching based on its implications professional educators in in rural areas in multigrade classesriverside. This involved the following research question: For what reasons and educational practices that constitute the teaching profession of educators from the field in multigrade classes riverside? This, from the perspective of the discussion of knowledge base, while professional competence of professionalism that transcends the domain of skills and techniques and emerges from the interaction between moral obligation and commitment to the community where the school is; professional development of teaching from the standpoint of studies of Rural Education. This study was conducted under the framework of investigative historical and dialectical materialism and the contour ethnographic research in order to characterize the work in the multigrade teaching riparian profiles and attitudes of educators teaching intervention in the schooling process, institutional contribution to the teachers in the field and some aspects of community organization with respect to the structuring of schooling processes and dynamics of human development in rural areas.